The impact of Lean bundles on hospital performance: does size matter?. Issue 8 (10th October 2016) - Al-Hyari, Khalil; Abu Hammour, Sewar; Abu Zaid, Mohammad Khair Saleem; Haffar, Mohamed
Abstract : Purpose: The purpose of this paper is to study the effect of the implementation of Lean bundles on hospital performance in private hospitals in Jordan and evaluate how much the size of organization can affect the relationship between Lean bundles implementation and hospital performance. Design/methodology/approach: The research is considered as quantitative method (descriptive and hypothesis testing). Three statistical techniques were adopted to analyse the data. Structural equation modeling techniques and multi-group analysis were used to examine the research's hypothesis, and to perform the required statistical analysis of the data from the survey. Reliability analysis and confirmatory factor analysis were used to test the construct validity, reliability and measurement loadings that were performed. Findings: Lean bundles have been identified as an effective approach that can dramatically improve the organizational performance of private hospitals in Jordan. Main Lean bundles – just in time, human resource management, and total quality management are applicable to large, small and medium hospitals without significant differences in advantages that depend on size. Originality/value: According to the researchers' best knowledge, this is the first research that studies the impact of Lean bundles implementation in healthcare sector in Jordan. This research also makes a significant contribution for decision makers in healthcare to increase their awareness of Lean bundles.